(untitled) (Transport systems and technologies, 2018)
The paper dependences of the influence of train arrival intervals to full and systematic technological failures of station parks have been researched. For practical implementation the method of justification minimum reserve capacity has been created, which, unlike existing ensures appropriate probability of timely acceptance of trains and their reasonable time delay on station’s tracks